2009
DOI: 10.1159/000268288
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Responses in IRAK-4-Deficient Neutrophils

Abstract: Human neutrophils were found to express all known Toll-like receptors (TLRs) except TLR3 and TLR7. IRAK-4-deficient neutrophils were tested for their responsiveness to various TLR ligands. Essentially all TLR responses in neutrophils, including the induction of reactive oxygen species generation, adhesion, chemotaxis and IL-8 secretion, were found to be dependent on IRAK-4. Surprisingly, the reactivity towards certain established TLR ligands, imiquimod and ODN-CpG, was unaffected by IRAK-4 deficiency, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…These findings indicate that the patient cells had a completely normal capacity to generate reactive oxygen species (ROS) and normal recognition and signaling for these immediate responses. 17,25 Adhesion and chemotaxis upon activation by TLR ligands or chemoattractants such as complement fragment C5a, PAF, or the chemokine IL-8, were all normal (not shown). Leukocytes from the patient and a control subject were incubated overnight with the indicated stimuli.…”
Section: Org Frommentioning
confidence: 99%
“…These findings indicate that the patient cells had a completely normal capacity to generate reactive oxygen species (ROS) and normal recognition and signaling for these immediate responses. 17,25 Adhesion and chemotaxis upon activation by TLR ligands or chemoattractants such as complement fragment C5a, PAF, or the chemokine IL-8, were all normal (not shown). Leukocytes from the patient and a control subject were incubated overnight with the indicated stimuli.…”
Section: Org Frommentioning
confidence: 99%
“…Neutrophils isolated from these patients fail to produce an oxidative burst in response to different TLR ligands. Another study, which included a single IRAK4-deficient patient, showed that these neutrophils also fail to respond to TLR ligands, but killing of bacteria and fungi was unaffected (van Bruggen et al, 2010). This suggests that recognition of microbial ligands is redundant in neutrophils or that some bacteria developed strategies to circumvent TLR recognition.…”
Section: Microbial Recognitionmentioning
confidence: 99%
“…aureus often causes diseases in CGD patients (around 30% of all infections), followed by Aspergillus, Salmonella, Candida, and Serratia species (Winkelstein et al, 2000;van den Berg et al, 2009). The localization and outcome of the infections differ depending on the infecting microbe: Aspergillus species mostly cause infections in the lungs and brain with a high mortality rate.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…105 However, TLR signaling is not essential for anti-Candida activity of human PMN as shown by testing PMN from patients with IRAK4 deficiency, a central component in TLR signaling. 106 Finally, neutrophils constitutively express FcgR; specifically, FcgRIII (CD16) activation can initiate characteristic neutrophil activation mechanisms, e.g., degranulation and respiratory burst. 107,108 In summary, while CR3 seems to play a central role multiple receptors may contribute to the interaction of PMN with C. albicans.…”
Section: The Various Roles Of Neutrophils In C Albicans Sepsismentioning
confidence: 99%